THE EFFECT OF PRODUCT QUALITY AND CONSUMER DISSATISFACTION ON WARDAH LIPSTICK BRAND SWITCHING BEHAVIOR IN PADANG STATE UNIVERSITY STUDENTS: Pengaruh Kualitas Produk dan Ketidakpuasan Konsumen terhadap Perilaku Peralihan Merek Lipstik Wardah pada Mahasiswa Universitas Negeri Padang - Nabila Noer Istiqamah; Annur Fitri Hayati (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
The purpose of this study was to investigate how it affects the quality of the poduk and consumer dissatisfaction with the brand switch on Wardah lipsticks. This study uses a causal research design and quantitative methodology. The population of this study consisted of Padang State University students who had worn Wardah lipstick and switched brands. Sampling was 100 and the sampling method was purposive sampling. The findings of the study revealed that (1) there was a significant negative influence of product quality on the brand change of Wardah lipstick products in female students at Padang State University. (2) consumer dissatisfaction has a significant positive influence on the brand change of Wardah lipstick products in Padang State University students. (3) the significant influence between product quality and consumer dissatisfaction on the switch of Wardah Lipstick Brand to female students at Padang State University